Exploratory MRI measures after intravenous autologous culture-expanded mesenchymal stem cell transplantation in multiple sclerosis. Issue 2 (June 2019) - Feng, Jenny; Offerman, Erik; Lin, Jian; Fisher, Elizabeth; Planchon, Sarah M; Sakaie, Ken; Lowe, Mark; Nakamura, Kunio; Cohen, Jeffrey A; Ontaneda, Daniel
Background: Mesenchymal stem cells (MSC) have immunomodulatory and neuro-protective properties and are being studied for treatment of multiple sclerosis (MS). Tractography-based diffusion tensor imaging (DTI), cortical thickness (Cth) and T2 lesion volume (T2LV) can provide insight into treatment effects. Objective: The objective of this study was to analyse the effects of MSC transplantation in MS on exploratory MRI measures. Methods: MRIs were obtained from 24 MS patients from a phase 1 open-label study of autologous MSC transplantation. DTI metrics were obtained in lesions and normal-appearing white matter motor tracts (NAWM). T2LV and Cth were derived. Longitudinal evolution of MRI outcomes were modelled using linear mixed effects. Pearson's correlation was calculated between MRI and clinical measures. Results: Lesional radial diffusivity (RD) and axial diffusivity (AD) decreased pre-transplant and showed no changes post-transplant. There were mixed trends in NAWM RD and AD pre/post-transplant. Transplantation stabilized T2LV growth. NAWM RD and AD correlated with Cth, T2LV and with leg and arm function but not with cognition. Lesional DTI demonstrated similar but less robust correlations. Conclusions: Microstructural tissue integrity is altered in MS. DTI changes pre-transplant may be influenced by concomitant lesion accrual. Contributor to DTI stabilization post-transplant is multifactorial. DTI of major motor tracts correlated well with clinical measures, highlighting its sensitivity to clinically meaningful changes.